GYMNASTICS IN HIGHER EDUCATION: (RE)DEFINING FORMATION CONTEXT AND PROFESSIONAL PERFORMANCE. (Fiep Bulletin - online, 2013)
The aim of this paper is to broach the “Gymnastics in Higher Education” subject. It is necessary to accentuate the process of curricular formation that has involved all Higher Education Institution in the Country. This process was initiated based on legal orientations and the courses' academic autonomy. This process is highly necessary so we can reflect about the profile and the professional work field of those who join the formation course of Physical Education. Some questions are important so we can take a position for the focused theme: Which Curricular Project are we talking about? What is the professional profile suggested for the formation? What is the established theoretic matrix? What are the goals for the formation of the Physical Education professional? Based on these reflections we look to the Pedagogic Political Project of the Licensure course in Physical Education at State University of Londrina UEL - where we work as teachers. The aim of the present article is to show how Gymnastics is organized in the curriculum taken in consideration based on the Licensure course's profile and goals.
Keywords: Gymnastics; Curriculum; Physical Education